Electron and hole spectra in the superlattice of cylindrical quantum wires - Tkach, M.V.; Pronyshyn, I.V.; Makhanets, A.M.; Zegrya, G.G.; Golovach, V.N. (Condensed Matter Physics, 1999)
Electron and hole spectra in n β-HgS cylindrical quantum wire superlattice in β-CdS matrix are calculated within the method of augmented plane waves. The energy term determined by the movement of quasiparticles in direction perpendicular to the axial axis of the wire is presented by the alternating zones with a positive and a negative effective mass. The degeneration on the magnetic quantum number outside Г point of Brillouin zone is taken off when the potential of the superlattice quantum wires is taken into account. The ground zones energy dependence of plane quasiparticle movement on the radii of the quantum wires as well as the distance between the wires are investigated. Методом приєднаних плоских хвиль розрахованi спектри електронiв i дiрок у надгратцi цилiндричних квантових дротiв β-HgS у матрицi β-CdS. Складова енрергiї, що обумовлена рухом квазiчастинок у напрямку перпендикулярному аксiальнiй вiсi дроту являє собою чергування зон з додатньою та вiд’ємною ефективною масою. Врахування потенцiалу надгратки квантових дротiв приводить до зняття виродження за магнiтним квантовим числом при вiдходi вiд точки ❳ зони Брiлюена. Дослiдженi залежностi енергiй основних зон плоского руху квазiчастинок вiд радiуса квантових дротiв i вiдстанi мiж дротами.